2012
DOI: 10.7314/apjcp.2012.13.6.2523
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Febrile Neutropenic Patients on Granulocyte Colony Stimulating Factor in a Tertiary Care Hospital

Abstract: Introduction: Febrile neutropenia is a relatively frequent event in cancer patients treated with chemotherapy and improvement in absolute neutrophil count (ANC) has been linked directly to improved outcome. Evaluation of granulocyte colony stimulating factors (GCSFs) for treatment has shown reduced incidences of episodes of prolonged neutropenia and protracted hospitalization. To determine absolute neutrophil counts with GCSF in febrile neutropenic cancer patients admitted to a tertiary care centre and to co-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
4
1
Order By: Relevance
“…In another study, Osmani et al found the mean ANS value to be 127/mm³ in the mor-tality group and reported a statistically significant relationship between ANS and mortality. 12 Our findings contradict those reported in the literature. We observed no statistically significant differ-ence in the median ANS values of the mortality and non-mortality groups (85/mm³ and 100/mm³, respectively).…”
Section: Discussion Discussioncontrasting
confidence: 99%
“…In another study, Osmani et al found the mean ANS value to be 127/mm³ in the mor-tality group and reported a statistically significant relationship between ANS and mortality. 12 Our findings contradict those reported in the literature. We observed no statistically significant differ-ence in the median ANS values of the mortality and non-mortality groups (85/mm³ and 100/mm³, respectively).…”
Section: Discussion Discussioncontrasting
confidence: 99%
“…Patients with mild and moderate neutropenia had better outcome with no deaths reported among them compared to profound neutropenia. This is in agreement with Osmaniet al who recorded that patients with profound neutropenia were more likely to die than patients with severe and moderate neutropenia [12].…”
Section: Discussionsupporting
confidence: 92%
“…This is unlike what reported by Osmani et al where 43.5%, 26% and 31% of their patients presented by profound, severe and moderate neutropenia respectively. This difference may attributed to high percent of hematological malignancies among their patients which known by their aggressive chemotherapy and more bone marrow suppression more than solid tumors [12].…”
Section: Discussionmentioning
confidence: 99%
“…The finding was supported by a previous observational study in Pakistan and India. 47 , 48 This might be because the use of filgrastim accelerates the production and circulating of neutrophils by reducing the transient time from stem cells to mature neutrophils. 49 In this study, the majority (95%) of the patients were treated with combined antibiotics and 30% of prescription was inappropriate.…”
Section: Discussionmentioning
confidence: 99%